Pengembangan Media Pembelajaran Video Tutorial Nail Art 3 Dimensi Tema Flora pada Mata Kuliah Perawatan Tangan dan Kaki - Siti Nurjanah; Aniesa Puspa Arum; Titin Supiani (Journal on Education, 2024)
This research aims to develop learning media in the form of video tutorials that are used as 3-dimensional nail art learning media in hand and foot care courses, so that it can be an additional motivation and reference for students and students in the learning process so that it can facilitate learning without being limited by space and time. The method used is research and development (R&D) which is used to produce and develop a product. This study uses the ADDIE model (but limited to the implementation stage). The researcher conducted a validation test on lecturers, material experts, and media experts to determine the feasibility of the video tutorial developed. The results of the research and development of this tutorial video have been said to be very feasible. The feasibility was obtained from the results of the validation test from material experts with a score of 82.5% and the results of the validation test from media experts with a score of 86.66%. The researcher conducted a practicality test on students who have taken the Hand and Foot Care course (nail art material) in the Cosmetology Education Study Program class of 2020 and 2021. The results of the practicality test on students with 30 respondents, received a score of 88.2% in the category of Very Practical for learning. So it can be concluded that the development of Flora-themed Nail Art 3D tutorial video learning media is very feasible and practical, so that it can be used in learning without being limited by space and time, because it can be used for independent learning.